Synthesis of Some Bromo-Substituted 3-Aroyl Flavanones and Flavones - P. R. Mahalle; N. T. Khaty (E-Journal of Chemistry)
A series of bromo-substituted 3-aroyl flavanons and flavones have been synthesized. The identities of the new compounds synthesized have been developed on the basis of usual chemical transformation and IR, NMR spectral studies.